Drawing for product designers - Henry, Kevin, ....- (London : Laurence King, 2012)
This is both a practical and theoretical guide to the visualization techniques used by contemporary product designers, including freehand sketching, digital rendering, information graphics, and presentation skills. Hundreds of hand-drawn sketches and computer models have been specially created to demonstrate critical geometry and show how to develop sketches into finished illustrations. Practical tutorials give guidance in creating simple and complex forms, as well as rendering and providing context using scenarios and storyboards. Insightful case studies of leading designers illustrate the full range of different visualization options available.
Includes bibliographical references and index.
Keywords: Computer-aided design; Product design; Drawing -- Technique